Mooring Pile of Floating Platform Dynamic Reliability Analysis under Wind and Wave Vibration: A Monte Carlo-Based Numerical Case Study - Tianyu Chen; Tonggai Yang; Yanbo Zhu; Qiong Hu (Advances in Civil Engineering)
As an important infrastructure, the floating platform plays a significant role in coastal and oceanic development. The single-point mooring system anchored by piles has been widely used to support floating offshore platforms. However, few studies in the field of floating structures focused on the dynamic reliability and mechanical analysis of the mooring pile foundation under wind and wave vibration. A Monte Carlo-based mooring pile reliability analysis method was introduced in this paper, which could consume the calculation source significantly. Based on the Monte Carlo simulation, the dynamic reliability of the mooring pile system of the floating platform was analyzed and discussed. Finally, considering the material cost, the design of the mooring pile of floating platform was optimized. The simulation work presented here also will contribute to a deeper understanding of civil engineering works’ pile foundation.